Pengaruh Penambahan Pasta Kacang Merah Terhadap Sifat Organoleptik, Kadar Gizi Dan Angka Lempeng Total Mikroba Sosis Analog Kamete (Kacang Merah Tempe) - Novi Aulia; Made Darawati; igde Widiada; iketut Swiryajaya (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. In West Nusa Tenggara (NTB) the incidence of stunting was still high, which increased from 2016 (30.0%) and 2017 (37.2%). Children with poor nutrition, especially protein, will cause growth disruption so that children are less nutritious and stunted. Objective of the research: To determine the effect of adding bean paste to organoleptic properties, nutrient content and total plate number of analogue sausage microbes Kamete (Tempe red beans). Research Methods. Experimental Method was carried out in a laboratory with a complete randomized design of one factor, namely the addition of red bean paste from the weight of tempeh flour consisting of 5 treatment levels (50%, 75%, 100%, 125%, and 150%) repetition 3 times . Organoleptic properties test using hedonic test, the results of the best organoleptic tests were tested for nutrient levels (water, ash, protein, fat, carbohydrate) and total microbes. Research Result. The proximate test results at the level of treatment of t5 analogue kamete sausages are containing 60.75% moisture content, 2.26% ash content, 8.38% fat, 8.74% protein, and 19.80% carbohydrate. Test results for moisture content, ash content and fat content have met the quality requirements of the Indonesian National Standard with a maximum water content of 67%, maximum ash content of 3%, maximum fat content of 25, while protein content and carbohydrate levels have not met the Indonesian National Standard, namely minimum protein 13% and carbohydrates up to 8%. Conclusion. The test results for the analogue microbial sausage kamete total plate number at the t5 treatment level of 2.6x102 colonies / ml meet the Indonesian National Standard because it is still below the threshold of the quality requirements of kamete analog sausages in the Indonesian National Standard which is a maximum of 105 colonies / g.